The Relationship between the Concept of a Person in the Philosophical Anthropological Sense and a Legal Subject as a Holder of Personality and Human Rights - Peročević, Katarina (Pázmány Law Review, 2023)
The legal status of human beings has been the subject of discussion by numerous theoreticians in the history of philosophy and law, from Kelsen and Fuller, to Dewey and Arendt, natural law and positive law theoreticians. Throughout history, the legal status of a person has been an interesting mixture of reality and abstraction, naturalistic and legal-technical perspectives. Different theoretical interpretations have always resulted in different practices. The paper aims to offer a more detailed picture of approaches to the legal status of a natural person as a holder of human and personality rights as well as to point out the importance and reasons for the recognition of legal subjectivity of each human being.